Chronic regional intestinal inflammatory disease: A trans-species slow infection?. (February 2019) - Balseiro, Ana; Perez, Valentin; Juste, Ramon A.
Highlights: Chronic enteritis throughout mammal species fit in a common pathological framework. Pathological framework matches a definition of slow infection. Unspecific innate response to infectious agent could explain pathological features. Filling the gaps in proposed framework could confirm the mycobacterial IBD hypothesis. Abstract: Crohn's disease and ulcerative colitis in humans and paratuberculosis in domestic and wild ruminants can be defined as chronic regional intestinal inflammatory diseases (CRIID). This review is a literature overview on these diseases in humans, non-human primates, dogs, cats, rabbits, equids and ruminants with a focus on pathological and microbiological features aimed identifying common characteristics that could lead to a unified pathological classification for a better understanding of their mechanisms and causes. The result is a framework of inflammatory forms throughout the different species indicative of common mechanisms of the slow infection type characterized by a time course varying from weeks to months or even years, and where the inflammatory component would be more prominent in the intestinal interphase between host and environment and be morphologically characterized by an infiltrate ranging from lymphoplasmacytic to histiocytic. This should provide new insights for causation demonstration and therapeutic approaches in human IBD.